Maintaining essential healthcare services in Addis Ababa during COVID-19: A qualitative study - Fenta, E.H.; Tassew, B.; Abera, A.; Wolde, F.B.; Legesse, M.; Pulford, J.; Mor, Siobhan M.; Kaba, Mirgissa (2024)
Background: Worldwide, health systems have been challenged by the overwhelming demands of the COVID-19 pandemic. In Ethiopia, maintaining essential health services during the COVID-19 pandemic is critical to preventing severe outcomes and protecting the gains made over the past years in the health sector. This project aims to explore the health system’s response to maintaining essential healthcare services in Addis Ababa, Ethiopia.